Pengembangan Konsep Wisata Apung Kampung Nelayan Pesisir Balikpapan - Ristianti, Novia Sari (Ruang, 2015)
This study aims to provide recommendations structuring concepts in the coastal fishing village Balikpapan using the concept of a floating tour. Settlements fishing village located around tourism destinations that have environmental issues with the availability of public infrastructure and facilities are inadequate and residential neighborhoods that have the selling value of travel. Moreover, with the Spatial Plan (RTRW) Balikpapan years 2012-2032 that have set up a new space for the benefit of economic investment in the form of Regions Coastal Road Balikpapan hence the need for structuring the slums fishermen along the coast of the city of Balikpapan. Therefore, the need for the concept of slum settlements of fishermen along the coast of Balikpapan in favor of realizing the coastal road. The concept led to the arrangement of settlement activities that are sustainable both in terms of economic, environmental and social coastal communities through the realization of SMART ECO-VILLAGE. This concept carries the principle of sustainability in terms of economic, environmental and social but still adopt the culture and customs of fishing communities which are then packaged in settlements through the concept of rural tourism development.